The impact of nostalgia and probability markers on the effectiveness of advertising creative strategies - Langaro, D.; Loureiro, S. M. C.; Contreiras, M (Journal of Promotion Management, 2020)
The current study intends to explore the boundaries of nostalgia themed advertising combined with probability markers. An experimental design was implemented with 575 valid responses obtained. The findings validate nostalgia themed advertising as a creative strategy associated to positive effects on brand attitude and purchase intentions among consumers with “high” past brand attachment. Past brand attachment emerges as an important construct as the effects significantly differ between “high” and “low” conditions. The use of probability markers, however, did not confirm the expected incremental effects on nostalgia themed advertising, with results being comparable with advertisement with no probability marker. Moreover, the use of hedges and pledges seem to perform in a similar manner among the different types of purchase motivations and level of tolerance to ambiguity. Implications for practice, limitations and future studies are presented.